Molluscicidal and Larvicidal Potency of N-Heterocylic Analogs against Biomophalaria alexandrina Snails and Schistosoma mansoni Larval Stages - Sherin K. Sheir; Elshaymaa I. Elmongy; Azza H. Mohamad; Gamalat Y. Osman; Shimaa E. Bendary; Abdullah A. S. Ahmed; Reem Binsuwaidan; Ibrahim El-Tantawy El-Sayed (Pharmaceutics, 2023)
This work describes the synthesis of quinoline-based N--heterocyclic arenes and their biological evaluation as molluscicides against adult Biomophalaria alexandrina snails as well as larvicides against Schistosoma mansoni larvae (miracidia and cercariae). Molecular docking studies were demonstrated to investigate their affinity for cysteine protease protein as an interesting target for antiparasitics. Compound AEAN showed the best docking results followed by APAN in comparison to the co-crystallized ligand D1R reflected by their binding affinities and RMSD values. The egg production, hatchability of B. alexandrina snails and ultrastructural topography of S. mansoni cercariae using SEM were assessed. Biological evaluations (hatchability and egg-laying capacity) revealed that the quinoline hydrochloride salt CAAQ was the most effective compound against adult B. alexandrina snails, whereas the indolo-quinoline derivative APAN had the most efficiency against miracidia, and the acridinyl derivative AEAA was the most effective against cercariae and caused 100% mortality. CAAQ and AEAA were found to modulate the biological responses of B. alexandrina snails with/without S. mansoni infection and larval stages that will affect S. mansoni infection. AEAA caused deleterious morphological effects on cercariae. CAAQ caused inhibition in the number of eggs/snail/week and reduced reproductive rate to 43.8% in all the experimental groups. CAAQ and AEAA can be recommended as an effective molluscicide of plant origin for the control program of schistosomiasis.